Clinical, bioethical, and forensic medicine aspects of the treatment of genital ambiguities - Di Pietro, Maria Luisa (Medicina e Morale, 2000)
The ambiguity of external genitals may cause difficulties in the attribution of gender at birth, therefore dealing with such cases may be very problematic for health staff. Even now that gender diagnosis is made by ultrasonography diagnosis at a prenatal stage, decisions about how to behave are taken after birth. This article analizes clinical, bioethical, and forensic medicine aspects of the assignation of gender. After recalling the biological and cultural factors of sexual differentiation, some clinical pictures of intersexuality are illustrated. In the second part the Author examines the criteria for the treatment of genital ambiguities used until today (somatic criterion; criterion of medico-surgical practicability; criterion of prevalence), and proposes the diagnostic criterion.